The impact of research and innovation investment on Al- Arafah Islami Bank's financial performance - Shuborna, Rokhsana Nasrin (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.